Beginning iPhone Development with Swift 2 Exploring the iOS SDK - Mark, David; Topley, Kim; Nutting, Jack; Olsson, Fredrik; LAMARCHE, JEFF (Apress : Imprint: Apress, 2015)
This is the definitive guide to the Swift programming language and the iOS 9 SDK, and the source code has been updated to reflect Xcode 7 and Swift 2. There's up-to-date coverage of new Apple technologies as well as significant updates to existing material. You'll have everything you need to create your very own apps for the latest iOS devices. Every single sample app in the book has been rebuilt from scratch using the latest Xcode and the latest 64-bit iOS 9-specific project templates, and designed to take advantage of the latest Xcode features. Assuming little or no working knowledge of the new Swift programming language, and written in a friendly, easy-to-follow style, this book offers a complete soup-to-nuts course in iPhone, iPad, and iPod touch programming. The book starts with the basics, walking through the process of downloading and installing Xcode and the iOS 9 SDK, and then guides you though the creation of your first simple application. From there, you'll learn how to integrate all the interface elements iOS users have come to know and love, such as buttons, switches, pickers, toolbars, and sliders. You'll master a variety of design patterns, from the simplest single view to complex hierarchical drill-downs. The art of table building will be demystified, and you'll learn how to save your data using the iPhone file system. You'll also learn how to save and retrieve your data using a variety of persistence techniques, including Core Data and SQLite. And there's much more! What You Will Learn: Everything you need to know to develop your own bestselling iPhone and iPad apps Utilizing Swift playgrounds Best practices for optimizing your code and delivering great user experiences< What data persistence is, and why it's important Get started with building cool, crisp user interfaces How to display data in Table Views How to draw to the screen using Core Graphics How to use iOS sensor capabilities to map your world How to get your app to work with iCloud and more Who This Book is For:.